FORMATION OF INNOVATIVE PEDAGOGICAL ACTIVITY OF THE FUTURE NATURAL SCIENCES TEACHER - Красноштан, Ігорь; Манзій, О. (Modern engineering and innovative technologies, 2022)
The article emphasizes that innovative processes in education require new forms and mechanisms of interaction between theory and practice. Innovative pedagogical activity is considered, which creates new standards of personal-creative, individually direct